Effects of Diet, Aerobic Exercise, or Both on Non-HDL-C in Adults: A Meta-Analysis of Randomized Controlled Trials. (8th November 2012) - Kelley, George A.; Kelley, Kristi S.
Abstract : Purpose . To use the meta-analytic approach to examine the effects of diet (D), aerobic exercise (E), or both (DE) on non-high-density lipoprotein cholesterol (non-HDL-C) in adults. Methods . Randomized controlled trials in adults ≥18 years of age were included. A mixed-effect model was used to combine effect size (ES) results within each subgroup and to compare subgroups (Q b ). Heterogeneity was examined using the Q and I 2 statistics, and 95% confidence intervals (CI) were also calculated. Statistical significance was set at P ≤ 0.05, while a trend for statistical significance was set between P > 0.05, and ≤0.10. Results . A statistically significant exercise minus control group decrease in non-HDL-C was found for DE (7 ESs, 389 participants, x ¯ = - 11.1  mg/dL, 95%  CI = − 21.7 to −0.6, P = 0.04, Q = 2.4, P = 0.88, I 2 = 0 %), a trend for the D group (7 ESs, 402 participants, x ¯ = − 8.5  mg/dL, 95%  CI = − 18.6 to 1.6, P = 0.10, Q = 0.76, P = 0.99, I 2 = 0 %), and no change for the E group (7 ESs, 387 participants, x ¯ = 3.0  mg/dL, 95%   CI = − 7.1 to 13.1, P = 0.56, Q = 0.78, P = 0.99, I 2 = 0 %). Overall, no statistically significant between-group differences were found (Q b = 4.1, P = 0.12 ). Conclusions . Diet combined with aerobic exercise may reduce non-HDL-C among adults in some settings.